Factors influencing citizens' intention to participate in e-participation in Malaysia / Nasrah Hassan Basri - Hassan Basri, Nasrah (2023)
E-participation is a subset of e-government that focuses on citizen participation in promoting a more transparent and inclusive society. The advantages that society cangain from citizens participating in e-participation initiatives are extensively acknowledged in the literature. Understanding the influencing factors in e-participation adoption is crucial for developing programs that promote citizen participation. However, present research on the drivers of e-participation adoption in Malaysia is still lacking. This study attempts to identify influencing factors of citizens' intention to participate in e-participation by employing the theory of UTAUT, trust and affect. This study aims, first, to identify the factors that influence the citizens' intention to participate in e-participation. Second, to examine the significant relationship of each factor with the behavioural intention and finally, to examine the roles of citizens' age and gender as moderating effect on this relationship. This research adopted the mixed method with semi-structured interview as the qualitative approach and survey-based quantitative approach. Respondents in this thesis are Malaysian aged 21 years involving12 participants in the qualitative study and 418 respondents in the quantitative study. Thematic analysis and PLS-SEM were used for the data analysis in this study. The findings revealed that out of eight independent variables (Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Trust in Government, Trust in Internet Technology, Positive Affect and Negative Affect), however, only Trust in Internet Technology, Performance Expectancy, Facilitating Conditions, Social Influence and Positive Affect were identified to be significant. Furthermore, age and gender have no moderation effect towards the relationship. The research contributed to the body of knowledge by merging the concepts of the UTAUT, trust and affect model in e-participation services. Practically, the findings of this study help stakeholders and decision-makers to strategically design plans and programs to accelerate the e-participation services in Malaysia. This study, similar to other empirical studies, has several limitations including non-Internet users, employing only cross-sectional survey and focusing merely on predictive intention in Malaysia context. To address these limitations, the future research will involves surveying a larger sample population, conducting a longitudinal survey and lastly testing the model in different scope and context to validate the generalizability of the model.